THE EFFECTIVENESS OF TECHNOLOGICAL MEDIA IN TEACHING ENGLISH FOR HIGHER EDUCATION STUDENTS - Dafa Aulia Muslimatus Sahara; Yepi Sedya Purwananti (Sindoro: Cendikia Pendidikan, 2025)
Generation Z, who grew up in the digital era, strongly prefers using technological media as a learning tool. This research aims to determine the effectiveness of using technological media, such as Canva Simple Booklet and Kahoot Game, in learning Translation courses. This research is quantitative research using pre-experimental research methods. In this research, researchers collected data by conducting pre-tests, treatment, and post-tests. In the first session, students take a pre-test to understand the material on translation procedures before using technological media. Then, the researcher carried out treatment using Canva media based on the Simple booklet. Then, the researcher gave a post-test after the treatment was carried out. The result is increased student grades after using technological media as treatment. The average post-test value is higher than the pre-test value, namely 79.96% < 56.88%, and the significance is smaller than 0.05. From these values, it can be seen that the use of technological media is significantly effective for student learning.